2012
DOI: 10.1136/emermed-2011-200997
|View full text |Cite
|
Sign up to set email alerts
|

Current practices for paediatric procedural sedation and analgesia in emergency departments: results of a nationwide survey in Korea

Abstract: Current PSA for paediatric patients have not been appropriately applied in Korea. Unified PSA guidelines were rare in the hospitals surveyed, and many patients were not monitored over an appropriate duration, nor did they receive adequate medications for sedation by the best trained personnel. Therefore, the national PSA guidelines must be developed and implemented as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…. 임상 연구 또한 국제적인 저널에 발표되는 성과도 점차 증가하고 있는데, 현재까지의 주 연 구 분야는 소아의 소생술 관련된 연구와 함께 진정 및 진 통에 대한 역학 및 임상 연구에 집중되고 있다 [14][15][16]19) .…”
unclassified
“…. 임상 연구 또한 국제적인 저널에 발표되는 성과도 점차 증가하고 있는데, 현재까지의 주 연 구 분야는 소아의 소생술 관련된 연구와 함께 진정 및 진 통에 대한 역학 및 임상 연구에 집중되고 있다 [14][15][16]19) .…”
unclassified
“…In the study by Hodkinson et al, only 15.3% of ECs had written protocols [5] , whilst another similar but later study that was also conducted in Cape Town, reported that 87.5% of private-sector and 37.5% of public-sector emergency centres had written protocols [27] . In a Korean study, institutional guidelines and protocols were only available in 20% of centres [28] .…”
Section: Discussionmentioning
confidence: 99%
“…M OST GUIDELINES RECOMMEND evaluating and assessing patients carefully before performing PSA to improve patient comfort and reduce AEs. 6,8,9,13 First, they recommend that EPs assess the patients' needs for analgesia, anxiolysis, immobility, or some combination of the three.…”
Section: Evaluation and Assessmentmentioning
confidence: 99%
“…The availability and common use of sedative and analgesic agents differ depending on region or country. 2,6 As a result, emergency medicine societies in some countries have published different policy statements and guidelines specific to the ED practices in their respective countries. 1,7,8 The European Society of Anesthesiology and European Board of Anesthesiology also published PSA guidelines for adults.…”
Section: Introductionmentioning
confidence: 99%